Measurement of the Zγ→νν̄γ Production Cross Section and Limits on Anomalous ZZγ and Zγγ Couplings in pp̄ Collisions at s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (American Physical Society (APS), 2009)
We present the first observation of the Zγ→νν̄γ process at the Fermilab Tevatron at 5.1standard deviations significance, based on 3.6fb-1 of integrated luminosity collected with the D0 detector at the Fermilab Tevatron pp̄ Collider at s=1.96TeV. The measured Zγ production cross section multiplied by the branching fraction of Z→νν̄ is 32±9(stat+syst)±2(lumi)fb for the photon ET>90GeV. It is in agreement with the standard model prediction of 39±4fb. We set limits on anomalous trilinear Zγγ and ZZγ gauge boson couplings, most of which are the most restrictive to date. © 2009 The American Physical Society.